2015
DOI: 10.1017/s0963548315000188
|View full text |Cite
|
Sign up to set email alerts
|

Universality of Graphs with Few Triangles and Anti-Triangles

Abstract: We study 3-random-like graphs, that is, sequences of graphs in which the densities of triangles and anti-triangles converge to 1/8. Since the random graph G n,1/2 is, in particular, 3-random-like, this can be viewed as a weak version of quasirandomness. We first show that 3-random-like graphs are 4-universal, that is, they contain induced copies of all 4-vertex graphs. This settles a question of Linial and Morgenstern [9]. We then show that for larger subgraphs, 3-random-like sequences demonstrate a completely… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…(1) In a follow up paper, Hefetz and Tyomkin [10] settle Problem 1 in the above list and make several additional interesting contributions to this area. (2) We have recently made some progress on Problem 8 above.…”
Section: Notes Added In Proofmentioning
confidence: 99%
“…(1) In a follow up paper, Hefetz and Tyomkin [10] settle Problem 1 in the above list and make several additional interesting contributions to this area. (2) We have recently made some progress on Problem 8 above.…”
Section: Notes Added In Proofmentioning
confidence: 99%
“…More recently, Linial and Morgenstern [10] showed that every sequence of graphs with t 0 + t 3 asymptotically minimal is 3-universal. Hefetz and Tyomkyn [7] then proved that such sequences are 4-universal, but not necessarily 5-universal, and moreover that any sufficiently large graph H can be avoided by such a sequence.…”
Section: Introductionmentioning
confidence: 99%